Reconstruction of Laboratory Activity Design Using Vee Diagram Analysis on Blood Type Test Based on ABO System in High School - Indriyani Amalia; Widi Purwianingsih; Kusnadi; Bambang Supriatno; Amprasto (Quagga: Jurnal Pendidikan dan Biologi, 2025)
Practicum is a series of activities that allow students to apply their skills to produce proof of a concept being studied, practicum focuses on the design of laboratory activities (DKL) that are first prepared by educators or school institutions. The purpose of this study was to analyze and reconstruct DKL blood type tests based on the ABO system taken from a collection of DKL at a school, the DKL analysis used an instrument based on the Novak & Gowin (1984) vee diagram. The method used in this study was descriptive qualitative, sampling was carried out by purposive sampling with one DKL blood type test ABO system taken from the practicum guidelines at a school compiled by the science lab team. Research activities follow the ANCOR stages (Analysis, Trial and Reconstruction). The results of the analyzed DKL research showed a value of 50% which means it is sufficient to be used, but there are deficiencies in the focus questions, records/data transformations, knowledge claims that are not in accordance with the vee diagram, so that a reconstruction is carried out which is expected to optimize the DKL in accordance with the vee diagram according to Novak & Gowin (1984) used by students and can support the objectives of the practicum activities.